Analisis variasi pipa penstock terhadap kecepatan inlet turbin pada PLTMH Boonpring menggunakan CFD - Rahmandhika, Andinusa; Mokhtar, Ali; Adi Putra, Bagus; Achmadi, Sentot (Universitas Muhammadiyah Metro, 2024)
The development of renewable energy is a necessity in order to reduce the consumption of fossil energy. One of the alternative technologies to obtain sustainable energy resources is to use a Micro Hydro Power Plant (PLTMH). In order to obtain high-efficiency power, it is necessary to analyze the maximum head and discharge values. In this study, an analysis of variations in the design of the penstock pipe from the forebay was carried out to obtain the highest velocity value for rotating the water turbine. The method used in this research is a simulation using ANSYS Fluent software. Based on the results obtained, the highest velocity values were obtained for penstock numbers 2 and 4. Pipe elevation causes the flow velocity to increase smoothly. The branching at the inlet does not affect the velocity value but increases the possibility of a vortex which is detrimental to the flow leading to the turbine.